Laxative overuse in geriatric patients: a growing concern - Ashraf, Asma; Waqar, Khushbakht (Journal of the Pakistan Medical Association, 2025)
Madam, by definition, a laxative is any medicinal substance actively used for treating chronic constipation by softening stools, facilitating their passage, and stimulating bowel movements. Chronic constipation is a major health implication and most commonly affects the elderly population. Laxatives are widely used by geriatric patients, with up to 20% of the geriatric population in the United Kingdom relying on them (Petticrew et al., 2001). Studies have shown that regular consumption of laxatives can lead to a gradual increase in dose over time, eventually causing dependence. A major concern arises when the intestines become atonic, losing their natural physiological function and becoming reliant on laxative-induced stimulation for bowel evacuation. The U.S. Food and Drug Administration (FDA) warns that exceeding a single dose of sodium phosphate—commonly found in laxatives—within 24 hours for constipation relief may lead to severe complications, including organ failure and death (2). A study conducted in Pakistan by Saleem et al. identified polypharmacy and self-medication, including the unsupervised use of laxatives, as critical health concerns among elderly patients (3). Many patients purchase and use these medications without medical guidance or a prescription. Other studies have also highlighted the life-threatening effects of laxatives. A 2010 study by Roerig et al. highlighted the adverse effects of laxative abuse, including water and electrolyte imbalances and cardiovascular complications (4). A 2019 study published in Drugs & Aging highlighted significant concerns about the lack of robust evidence regarding the safety and efficacy of laxatives in older adults (5). Apart from being affordable, laxatives are frequently prescribed and readily dispensed over the counter, often without adequate supervision or monitoring. The Consensus Guidelines on Constipation in Adults in Pakistan note that, while international data on constipation management is available, it often fails to consider the cultural and socioeconomic factors influencing disease management in Pakistan (6). Therefore, a safer approach is to include lifestyle and dietary modifications in the primary treatment for constipation. For chronic constipation, laxatives should be used under the guidance of healthcare providers. A key intervention involves reducing laxatives and transitioning to safer alternatives, such as fibre supplements (Pont & Fisher, 2019). —Continue